Effectiveness of the addition of visual aids to conversational preoperative education in glaucoma filtering surgery: A randomized controlled trial - Peimin Lin; Laiwen Lv; Ruqing Tang; Dehua Li; Xiaoxuan Chen; Jie Fang; Zhenggen Wu; Chukai Huang; Kusheng Wu (Heliyon)
Background: This study aimed to evaluate the impact of preoperative visual aids on anxiety and pain management in patients with low educational backgrounds undergoing glaucoma filtering surgery. Methods: A randomized, single-blinded, single-center clinical trial was conducted at a tertiary eye hospital in Shantou, China. Patients scheduled for glaucoma filtering surgery were randomly assigned to either a conventional oral education group or a visual aids group. Anxiety levels, pain scores, blood pressure, and pulse rates were measured at multiple time points. Findings: The visual aids group demonstrated significantly lower anxiety levels (HAMA score: 19.6 ± 1.7 vs. 27.9 ± 3.1; p < 0.001) and pain scores (VAS: F = 174.628; p < 0.001) compared to the oral education group. Additionally, systolic blood pressure was significantly lower in the visual aids group (F = 6.373; p = 0.013). During the preoperative visit, patients in the oral education group asked significantly more questions (mean ± SD: 4.0 ± 1.3) compared to those in the visual aids group (mean ± SD: 0.75 ± 0.7; p < 0.001). However, their understanding of the surgery was notably lower than that of the visual aids group. The requirement for additional anesthesia due to pain was markedly higher in the oral education group, with 66.2 % (45/68) of patients needing extra anesthesia compared to only 4.6 % (3/65) in the visual aids group (p < 0.001). Furthermore, the ocular positioning compliance and cooperation during the surgery were significantly lower in the oral education group compared to the visual aids group (p < 0.001). Interpretation: The inclusion of visual aids in preoperative education significantly improves patient outcomes in glaucoma filtering surgery by reducing anxiety and pain and stabilizing physiological parameters. This approach is particularly beneficial for patients with lower educational backgrounds.